Reaksi Pasar atas Pengumuman Larangan Ekspor Crude Palm Oil dan Produk Turunannya - Cahyani, Dwi Ega; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 33 No 8 (2023)DO - 10.24843/EJA.2023.v33.i08.p04, 2023)
This research aims to determine the reaction of capital market investors to the announcement of a ban on the export of Crude Palm Oil (CPO) and its derivative products. This research uses an event study approach for 7 days of observation in 2022. Market reactions in this research are measured using Cumulative Abnormal Return (CAR). The population of this research is oil palm plantation companies listed on the Indonesia Stock Exchange in 2022. The sampling method uses a purposive sampling technique. The number of samples obtained was 20 companies. This research uses one sample t-test data analysis techniques. The results of data analysis show that investors in palm oil plantation companies reacted negatively to the announcement of a ban on exports of CPO and its derivative products. This proves that investors pay attention to external events that can influence company performance. Keywords: Market Reaction; Event Study; Abnormal Return; CPO Export Ban